Habitat use and abundance of an introduced population of the Japanese weasel (Mustela itatsi): Comparison with the native population - Kotaro Kubo; Taisei Tachikawa; Miki Hirose; Masami Hasegawa; Eiji Inoue (PLoS ONE, 2025)
Understanding habitat use and abundance is essential for elucidating the impact of invasive species. Invasive carnivores affect ecosystems by preying on native animals. In Japan, the Japanese weasel (Mustela itatsi) is native to the mainland but has been intentionally introduced to many small islands, including Miyakejima Island. We investigated the habitat use and abundance of invasive non-native Japanese weasels on Miyakejima Island via fecal surveys, and for comparison, performed similar surveys for their native conspecifics on Izu-Oshima Island. We constructed a generalized linear mixed model and estimated fecal abundance across the entire island based on the effect of vegetation type on their abundance. On Miyakejima Island, deciduous broadleaf and bamboo forests had positive effects on weasel abundance, whereas grasslands had a negative effect. Conversely, on Izu-Oshima Island, bare ground had a negative effect. Further, the estimated average fecal abundance across Miyakejima and Izu-Ohshima Islands, considering vegetation type, were 7.44 and 4.89 feces samples per km, respectively, suggesting that weasels are well adapted to Miyakejima Island. We also analyzed the fecal DNA of weasels in a specific area on Miyakejima Island and estimated non-native weasel density at 20 individuals per km2 (95% CI: 4.9–80) using genetic capture-recapture methods in the area. These findings enhance understanding regarding non-native species and may facilitate the formulation of countermeasures for their control.